High-performance solution-processable flexible and transparent conducting electrodes with embedded Cu mesh. Issue 16 (7th March 2018) - Han, Seolhee; Chae, Yoonjeong; Kim, Ju Young; Jo, Yejin; Lee, Sang Seok; Kim, Shin-Hyun; Woo, Kyoohee; Jeong, Sunho; Choi, Youngmin; Lee, Su Yeon
Abstract : Well-defined and highly conductive Cu mesh transparent electrodes are prepared by a vacuum-free solution process. Abstract : Alternative transparent and conducting electrodes (TCEs) that can overcome the practical limitations of the existing TCEs have been explored. Although network structures of metal nanowires have been investigated for TCEs because of their excellent performance, characteristics such as high junction resistances, poor surface roughness, and randomly entangled NW networks still pose challenges. Here, we report cost-effective and solution-processable metallic mesh TCEs consisting of a Cu-mesh embedded in a flexible PDMS substrate. The unprecedented structures of the Cu-mesh TCEs offer considerable advantages over previous approaches, including high performance, surface smoothness, excellent flexibility, electromechanical stability, and thermal stability. Our Cu-mesh TCEs provide a transmittance of 96% at 550 nm and a sheet resistance of 0.1 Ω sq −1, as well as extremely high figures of merit, reaching up to 1.9 × 10 4, which are the highest reported values among recent studies. Finally, we demonstrate high-performance transparent heaters based on Cu-mesh TCEs and in situ color tuning of cholesteric liquid crystals (CLCs) using them, confirming the uniform spatial electrical conductivity as well as the reproducibility and reliability of the electrode.